DISCOURSE ANALYSIS OF MERONYMY-BASED COHESION IN “THE NEW YORK TIMES” ON MAYOR WHITMIRE - Jelita (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study analyzes lexical cohesion in The New York Times article titled “Houston’s Mayor, John Whitmire, Thinks the Best Way to Lead Is to Keep His Head Down.” The research focuses on identifying and explaining the use of meronymy or part–whole relations that contribute to textual unity and coherence in the news. Using a qualitative descriptive design (Creswell, 2018), ten data samples containing meronymic relations such as city–streets, mayor–government, and citizens–community were analyzed. The results show that meronymy strengthens cohesion by linking smaller components to broader social and political contexts. This relation helps the journalist present complex issues—such as public safety and urban policy—in a clear and unified manner. The study highlights the role of meronymy as a cohesive strategy that enhances coherence and readability in news discourse.